DETERMINAN MINAT PENGGUNAAN DOMPET DIGITAL - Refais, Muhammad Agam; Aliyah, Siti (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the determinants of interest in using digital wallets, with a focus on perceived usefulness, ease of use, and trust as independent variables.Methods: The research focuses on OJK registered digital wallet users who have completed transactions. The sampling method used purposive sampling with 100 respondents. Data was collected through an online questionnaire using a 1-5 Likert scale. Data analysis included t-tests, F-tests, and the coefficient of determination (R²) to measure the strength of variable influence.Results: Through multiple linear regression analysis, it was found that these three variables have a significant influence both partially (t-test) and simultaneously (F-test). Individually, the perception of usefulness (t = 7.790; sig. 0.031), ease (t = 6.618; sig. 0.025), and trust (t = 5.170; sig. 0.000) have a positive impact on the interest in using digital wallets. Simultaneously, the F-test shows a value of 111.151 with a significance of 0.000, proving a significant joint effect. The coefficient of determination (R²) value of 65.8% indicates that these three variables can explain the majority of the variation in the interest in using digital wallets, while the remaining 34.2% is influenced by factors outside the scope of the study. Therefore, it can be concluded that the perceptions of usefulness, ease, and trust play an important role in shaping and increasing students' interest in using digital wallets. Keywords: Digital Wallet, Perceived Usefulness, Perceived Ease of Use, Perceived Trust, Usage Interest